CHARACTERISTICS OF THE GRAIN-SIZE COMPOSITION OF DEEP-WATER OCEANIC SEDIMENTS - Sval'nov V.N.; Alekseeva T.N. (My University, 2006)
The grain-size composition of nonlithified sediments in the Indian, Pacific, and Atlantic oceans is studied. Grain-size features of the major lithogenetic types of deep-water sediments are determined. The genetic interpretation of results obtained is given. Trends of the fractionation of sandy-silty and pelitic materials in pelagic zones of sedimentation basins are revealed. © Pleiades Publishing, Inc. 2006.